The Russian-Ukrainian earnings divide - Amelie F. Constant; Martin Kahanec; Klaus F. Zimmermann (Institute for the Study of Labor (IZA), 2006)
Ethnic differences are often considered to be powerful sources of diverse economic behavior. In this paper, we investigate whether and how ethnicity affects Ukrainian labor market outcomes. Using micro data from the Ukrainian Longitudinal Monitoring Survey (ULMS) and Oaxaca-Blinder decomposition of earnings, we find a persistent and rising labor market divide between ethnic Russians and Ukrainians throughout Ukraine's transition era. We establish that language rather than nationality is the key factor behind this ethnic premium favoring Russians. Our findings further document that this premium is larger among males than among females.
urn:nbn:de:101:1-20090825329
Keywords: 330; Arbeitsmarktdiskriminierung; Ethnische Gruppe; Russen; Ukrainer; Systemtransformation; Ukraine